Delação premiada: limites constitucionais à confiabilidade e corroboração - Jamilla Monteiro Sarkis (2018)
Delação premiada is a reality in Brazilians legal system. Regulated by the Law n. 12.850/13, this institution is highly influenced by the North American plea bargainings concept, despite the incompatibility between systems and legal traditions. Mainly after the so called Operação Lava Jato, this type of bargaining has followed plea bargainings trend to triumph over other methods of criminal evidence production. This work reflects a special concern about the position of the defendant identificated by an accomplice testimony in exchange of benefits, whose individual rights are not guaranteed by the law or object of judicial protection. As it will be demonstrated, there must be a significant change of rules to define constitutional limits to the delação premiadas reliability and corroboration. In this regard, the dissertation purpose is to deepen the study about its legal nature and corroboration rule, to establish parameters for its reliability from neuroscience and cognitive psychology, to conclude by inserting the defendant in the criminal procedures guarantee system.